2012
DOI: 10.1177/0731684412462755
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of pultruded glass fiber reinforced plastic after freeze–thaw cycling

Abstract: The use of pultruded fiber-reinforced plastics in civil infrastructure requires the long-term prediction of their mechanical properties, which should be based on understanding and estimating the processes in the structure under action of aggressive environmental factors: humidity and freeze–thaw cycles. This article reports on results of short-term exposure to severe freeze–thaw cycling in the temperature range from –30°C to 20°C of polyester-based glass fiber reinforced plastic both dry and wet. The effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 9 publications
1
12
1
Order By: Relevance
“…Gomez and Casto [15] also reported considerable reductions of flexural strength and stiffness of both isophthalic polyester or vinylester resins, particularly for the latter resin, which is in accordance with our results. The flexural strength results reported by Aniskevich et al [25] are in general agreement with our test data, in opposition to the flexural modulus which contrasts with our results; differences may be due to post-curing phenomena and matrix hardening caused by the exposure to low temperatures.…”
Section: Flexural Responsesupporting
confidence: 86%
See 2 more Smart Citations
“…Gomez and Casto [15] also reported considerable reductions of flexural strength and stiffness of both isophthalic polyester or vinylester resins, particularly for the latter resin, which is in accordance with our results. The flexural strength results reported by Aniskevich et al [25] are in general agreement with our test data, in opposition to the flexural modulus which contrasts with our results; differences may be due to post-curing phenomena and matrix hardening caused by the exposure to low temperatures.…”
Section: Flexural Responsesupporting
confidence: 86%
“…Despite some differences (in terms of materials, manufacturing process, and/or test conditions) between the present study and those performed by Karbhari et al [18] and Aniskevich et al [25], the range of variation in DMA results was similar. Fig.…”
Section: Effects Of Thermal Cyclescontrasting
confidence: 57%
See 1 more Smart Citation
“…5 As a result, adding carbon fibers or some other materials to reinforce PC has become one of the hot topics for researchers, and all the research results show that fibers can better reinforce the compression and bending strength. [6][7][8][9][10][11][12][13] However, the use of carbon fibers not only reinforces the mechanical strength of PC, but also produces a certain effect to the damping performance inevitably. Therefore, related scholars all over the world have conducted a series of research on the damping mechanism of carbon fiber-reinforced polymer concrete (CFRPC).…”
Section: Introductionmentioning
confidence: 99%
“…Felipe et al (2012) studied and analyzed about glass fiber reinforced plastic sheet under the environmental deterioration on its surface, when placed in a chamber built and also the observed the mechanical behavior when subjected to uniaxial tension. Aniskevich et al (2012) reported on short-term exposure to severe freeze-thaw cycling in the temperature range from -30°C to 20°C of polyester-based glass fiber reinforced plastic both dry and wet. The effect of freeze-thaw cycling of flat specimens cut from I-beam pultruded profile was estimated by use of three-pointbending tests and dilatometric investigation in the temperature range from 20°C to 125°C.…”
Section: Introductionmentioning
confidence: 99%